Nível de atividade física, comorbidades e idade de pacientes hipertensos - Bueno, Denise Rodrigues; Da Costa Rosa, Clara Suemi [UNESP]; Codogno, Jamile Sanches [UNESP]; Freitas Jr., Ismael Forte [UNESP]; Monteiro, Henrique Luiz [UNESP] (FapUNIFESP (SciELO), 2013)
Physical inactivity is associated with chronic diseases in older adults. There are different domains of physical activity, such as leisure and locomotion. This study investigate the associations between different domains of physical activity, comorbidities and aging in hypertensive adults. Participants included 192 hypertensive respondents classified in groups of active and insufficiently active for leisure-time, locomotion, occupation and total time. They were stratified in age groups. Waist circumference was measured and comorbidities were self-reported. The chi-square test analyzed these associations; a one-way ANOVA compared the age groups (significance at p <0.05). The mean total time and occupational physical activity were lower for groups ages over 60 and 70 years, respectively. Occupational activity was associated with age in the female group, and with cholesterol and diabetes in males, who also had physical activity of locomotion associated with waist circumference. Physical activity of hypertensive patients is associated with comorbidities in different age groups and sex.

No envelhecimento, hábito inativo está associado a doenças crônicas. Existem diferentes domínios da atividade física, tais como: tempo livre e locomoção. O objetivo foi analisar associações entre diferentes domínios de atividade física, comorbidades e idade em hipertensos. Foram entrevistados 192 hipertensos. Classificados em menos ativos e mais ativos para atividades no lazer, locomoção, ocupação e total e estratificados em grupos etários. A circunferência de cintura foi avaliada e comorbidades auto referidas. O teste Qui-quadrado analisou as associações e o teste ANOVA one way comparou os grupos etários, adotando significância estatística quando p<0,05. As médias de atividade física ocupacional e total foram menores para idade igual ou acima dos 60 e 70 anos, respectivamente. A atividade ocupacional esteve associada à idade em mulheres e, ao colesterol e diabetes em homens, que também tiveram atividade física de locomoção associada à circunferência de cintura. Em síntese a atividade física de hipertensos associa-se a comorbidades para diferentes grupos etários e sexos.
Physical activity level, comorbidities, and aging in hypertensive patients
Nivel de actividad física, las comorbilidades y el envejecimiento en pacientes hipertensos
Keywords: Age; Comorbidities; Hypertension; Physical activity